2015
DOI: 10.1007/s12010-015-1686-z
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Quercetin-Iron Complexes into Phosphatidylcholine or Phosphatidylethanolamine Liposomes

Abstract: It is well known that flavonoids can chelate transition metals. Flavonoid-metal complexes exhibit a high antioxidative and therapeutic potential. However, the complexes are frequently hydrophobic ones and low soluble in water, which restricts their medical applications. Integration of these complexes into liposomes may increase their bioavailability and therapeutic effect. Here, we studied the interaction of quercetin-iron complexes with dimyristoylphosphatidylcholine (DMPC) or palmitoyl-oleoyl phosphatidyleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Dietary flavonoids have modulatory effect on PMRS activity which is linked to their structural orientation (Singh et al 2016). Quercetin has been reported to interact with phosphatidylcholine and phosphatidylethanolamine head groups in the cell membrane bilayer through hydrogen bonds at low concentrations and hydrophobic tail region at high concentrations (Kim et al 2015). These interactions may induce changes in membrane fluidity of RBCs which are associated with transport system (Kumar et al 2016b;Sanna et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary flavonoids have modulatory effect on PMRS activity which is linked to their structural orientation (Singh et al 2016). Quercetin has been reported to interact with phosphatidylcholine and phosphatidylethanolamine head groups in the cell membrane bilayer through hydrogen bonds at low concentrations and hydrophobic tail region at high concentrations (Kim et al 2015). These interactions may induce changes in membrane fluidity of RBCs which are associated with transport system (Kumar et al 2016b;Sanna et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilicity of 1:2 and 2:3 complex (metal:ligand) is two and three times higher, respectively [53]. On the other hand, some works implied that quercetin in the membrane system can improve its availability for Fe(II) with subsequent complex formation [54].…”
Section: Influence Of Chelated Iron Ions On the Antioxidative Effect mentioning
confidence: 99%
“…Furthermore, metallocomplexes formed by iron chelation may display their own unique biological activities. Iron complexation affects their biochemical properties such as lipophilicity, membrane transport, or interactions with biomolecules [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction study of quercetin-iron complexes with dimyristoylphosphatidylcholine (DMPC) or palmitoyl-oleoyl phosphatidylethanolamine (POPE) multilamellar liposomes revealed that, during preparation, quercetin should be added first to the suspension of liposomes [115]. It was presumed that quercetin can increase the permeability of lipid bilayers to iron cations, showing ionophore activity toward iron cations.…”
Section: Liposomal Systemsmentioning
confidence: 99%